Gephyrin phosphorylation in the functional organization and plasticity of GABAergic synapses - Zacchi, Paola; Antonelli, Roberta; Cherubini, Enrico (Frontiers in Cellular Neuroscience, 2014)
Gephyrin is a multifunctional scaffold protein essential for accumulation of inhibitory glycine and GABAA receptors at post-synaptic sites. The molecular events involved in gephyrin-dependent GABAA receptor clustering are still unclear. Evidence has been recently provided that gephyrin phosphorylation plays a key role in these processes. Gephyrin post-translational modifications have been shown to influence the structural remodeling of GABAergic synapses and synaptic plasticity by acting on post-synaptic scaffolding properties as well as stability. In addition, gephyrin phosphorylation and the subsequent phosphorylation-dependent recruitment of the chaperone molecule Pin1 provide a mechanism for the regulation of GABAergic signaling. Extensively characterized as pivotal enzyme controlling cell proliferation and differentiation, the prolyl-isomerase activity of Pin1 has been shown to regulate protein synthesis necessary to sustain the late phase of long-term potentiation at excitatory synapses, which suggests its involvement at synaptic sites. In this review we summarize the current state of knowledge of the signaling pathways responsible for gephyrin post-translational modifications. We will also outline future lines of research that might contribute to a better understanding of molecular mechanisms by which gephyrin regulates synaptic plasticity at GABAergic synapses.